Studies on stick grasshoppers: New Proscopiini taxa from Colombia, Panama, and Costa Rica (Orthoptera: Proscopiidae) - Castañeda, Oscar J. Cadena (Zootaxa, 2025)
In this contribution to the study of stick grasshoppers, taxa included in Pseudoproscopia Bentos-Pereira, 2006 are described and redescribed, covering distributions in Central America, the Chocó Biogeographic Region, and the slopes of the inter-Andean valleys of Colombia. Rowellscopia gen. nov. includes two species: Rowellscopia septentrionalis (Bruner, 1905) comb. nov. and Rowellscopia panamensis (Bentos-Pereira & Rowell, 1999) comb. nov., from Costa Rica and Panama. The genus Albascopia Cadena-Castañeda & Cardona-Granda, 2015 is redescribed, comprising four species, one of which is new: Albascopia columbica (Brunner von Wattenwyl, 1890), Albascopia caldensis (Cadena-Castañeda & Cardona, 2015) comb. nov., Albascopia afroensis (Cadena-Castañeda & Cardona, 2015) comb. nov., and Albascopia baudoensis sp. nov., from the Andes and Pacific region of Colombia. Identification keys for the species are provided, and the taxonomy, morphology, and distribution of the studied taxa are discussed.